Psychometric properties of the Perceptual Aberration Scale and the Magical Ideation Scale in Spanish college students - Eduardo Fonseca-Pedrero (International Journal of Clinical and Health Psychology, 2009)
The vulnerability for schizophrenia-spectrum disorders appears to be expressed across a dynamic continuum referred to as schizotypy. The Wisconsin- Madison psychosis-proneness scales are among the most extensively used self-reports for its measurement; however, the psychometric properties have not been widely investigated in Spanish populations. The aim of this instrumental work was to study the reliability and validity of the psychosis-proneness scales Perceptual AberrationScale (PAS) and Magical Ideation Scale (MIS) in its adaptation into Spanish. The sample was composed of 737 college students with a mean age of 20.3 (SD = 3.3). The results indicated that both Wisconsin-Madison scales showed adequate psychometric properties. The construct validity analysis carried out on the matrix of polychoric correlations showed that both scales presented an essentially unidimensional solution. The Cronbach alpha coefficients were .96 (PAS) and .93 (MIS). The correlation between the total scores of both scales was .60. The Perceptual Aberration Scale andMagical Ideation Scale seem to be useful self-reports for the identification of subjects with a higher risk of developing schizophrenia-spectrum disorders. Future research should replicate these findings in samples of other nationalities, determine the contribution of each dimension in the transition to psychosis, as well as apply them in clinical practice along with endophenotypes.